Study on movements of labor share of national income in Singapore - Bai, Chong (2015)
With the development of technology and labor productivity, the topic of labor share and capital share has gained wide interest all over the world. Currently most scholars believe that there is a significant decreasing trend in labor share since 1980s. Karabarbounis and Neiman (2014) examined 59 countries and found out that 42 countries have downward trend of labor share. This paper focuses on Singapore and would like to test whether Singapore also exhibit declining trend of labor share since the economy of Singapore is different from other developed countries in terms of financial-centered industrial structure, low unemployment rate and stable economic growth environment. Moreover, this paper would like to examine the labor share in different industries so that it could be shown that whether there is difference between industries. The paper mainly focuses on 6 industries and has collected the data of Gross Domestic Product (GDP), average monthly wage and employment number for the preparation of calculating labor share for the period from 1995 to 2013. The industrial classification is mainly based on the Singapore Standard Industrial Classification but with some minor modification for the consideration of consistency. The result shows that unlike most countries, almost all industry’s labor share is relatively stable over the period except the Wholesale & Retail Trade sector. The paper then analyzes reasons of the stable labor share from 3 aspects, which are industrial structure, low unemployment rate and stable economic growth. All these factors contribute to the constant growth in Singapore’s labor share and economy.